The Use of Kahoot! Application to Teach English Vocabulary Learning in Rural Area - ST Ayu Surayya; Selamet Riadi Jaelani; Ilmiani Ilmiani (Pioneer: Journal of Language and Literature, 2023)
The purpose of this study was to find out the effectiveness of Kahoot! application in teaching vocabulary at the eighth grade of MTs NWDI Lepak in the academic year 2021-2022. This study refers to mix method where a pre-experimental design using one group pre-test and post-test was used to find out the effectiveness of using Kahoot!, then observation was used to find out the students’ attitude on Kahoot! The sample of this study was the eighth-grade students consisting of 30 students. The data were collected from students’ pre-test and post-test by using multiple tests. The data were analyzed by using SPSS version 22 for Windows. After submitting the data to a paired sample t-test, it was found that there was a significant difference in the mean score between the pre-test and post-test, t(df=22)= -14.31 at p=0.00 which meant that the alternative hypothesis was accepted and the null hypothesis was rejected. Thus, Kahoot! The application was significantly effective in teaching students’ vocabulary in the eighth grade of MTs NWDI Lepak in the academic year 2021-2022. Considering the process and result of this study, it was suggested that English teachers use this media in teaching English vocabulary, both in urban and rural areas.